APLIKASI AUGMENTED REALITY BERBASIS AGEN CERDAS SEBAGAI MARKETING COMMUNICATION PADA PROGRAM STUDI TEKNIK INFORMATIKA FTIK UNIVERSITAS SEMARANG - Nur Wakhidah; Astrid Novita Putri; Muhammad Zakki Abdillah (Universitas PGRI Semarang, 2017)
In this study, using Augmented Reality and Methods Markeless Video Animation, which is focused on Information Engineering Program Faculty of Information and Communication Technology at the University of Semarang. Communication in use for Media Marketing Communication at the Faculty of Information Technology and Communications there are several obstacles to the process of the communication campaign for new students to get the information they need to visit the information center part of the University of Semarang to request brochures, and other promotional media are on the website http: // ftik.usm.ac.id, banners, and newspaper media only limited information has not been a technology that combines state of reality or virtual engineering conditions. In order for the conditions created virtual become more real and displays overall excellence of the Information Engineering Program Faculty of Information and Communication Technology at the University of Semarang. By making use of augmented reality technology using the marker in the text Information Engineering Program of a model text, and video animation that can be displayed virtually using mobile phones both android, blackberry or iphone so that people will more easily attract and knowing full well what are the an advantage Informatics Engineering Program of the video display animation.Aplikasi It will be developed using the Unity 3D and Vuforia SDK. Keywords : Augmented Reality, Markeless, Video, Animation, Marketing